TINGKAT PENGETAHUAN ORANG TUA TENTANG KONSEP INFEKSI SALURAN PERNAFASAN AKUT (ISPA) TERHADAP UPAYA PENCEGAHAN ISPA ANAK - Sumartono, Yongky (STIKES Widyagama Husada, 2024)
Introduction: One of the diseases that often occurs in children is acute respiratory infection (ARI), the incidence rate of ARI according to WHO (world health organization) in children is around 48,325 in Indonesia, in East Java around 28.3%, in 2022 there will be 225 children ISPA at the Mojolangu health center. One of the causes of ISPA is influenced by living conditions, season, child's age, child's nutrition and parents' level of knowledge in caring for children. Method: This research uses a quantitative method with a sample of 70 parents taken using random sampling techniques. The instrument used was the ISPA knowledge questionnaire which had been tested for validity and reliability at 0.663, while the validity and reliability test results for the ISPA prevention questionnaire were 0.798. Results: The results of research that has been carried out show that 25 respondents have very good ISPA knowledge, 10 respondents have sufficient ISPA knowledge, while 22 respondents have very good ISPA prevention and 12 respondents have sufficient prevention. Conclusion: There is a relationship between parents' knowledge of preventing ISPA in children aged 1-4 years at the Mojolangu Community Health Center with a P value of 0.000 < 0.05.